Uric acid is an independent factor associated with endothelial dysfunction in type 2 diabetic patients with microalbuminuria - XIE Chao; TIAN Jie; LIANG Min; YE Pei-yi; KONG Yao-zhong (Linchuang shenzangbing zazhi)
Objective To study the relationship between uric acid and endothelial dysfunction in type 2 diabetic patients with or without microalbuminuria.Methods From March 2010 to May 2011,we recruited 149 cases of type 2 diabetic mellitus without macrovascular disease from3 affiliated hospitals of Southern Medical University（Nanfang hospital,Jiangdu hospital,Zhujiang hospital）.Patients were divided into two groups in term of the 24-h urinary microalbumin excretion rate:112 patients with 24-h urinary microalbumin excretion rateless than 30 mg was the DN（-）group,and37 patients with24-h urinary microalbumin excretion rate between30 mg and 300 mg was the DN（+）group.49 age-and gender-matched healthy people served as the control group.The demographic indexes,biochemical indexes,and the marker of endothelial dysfunction:soluble vascular cell adhesion molecule 1（sVCAM-1）were analyzed.Results Serum uric acid in DN（+）group was much higher than the other two group[DN（+）vsDN（-）vs health control=（370.3±116.1）μmol/L vs（334.2±100.0）μmol/L vs（324.5±63.7）μmol/L,P=0.083],sVCAM-1 level was significantly higher in DN（+）group than the other two groups[DN（+）vs DN（-）vs health control=（519.4±130.9）ng/ml vs（466.2±108.7）ng/ml vs（435.5±70.3）ng/ml,P=0.002],Multivariate regression analysis showed that serum uric acid was the only independent factor positively correlated to sVCAM-1 in DN（+）group（β=0.35,P=0.044）,but this relationship was not significant in DN（-）group（β=0.052,P=0.593）.Conclusions Serum uric acid was significantly higher in type 2 diabetic patients with microalbuminuria than that in healthy people,and significantly correlated to endothelial dysfunction,but this relationship was not significant in type 2 diabetes mellitus patients without microalbuminuria,suggesting that we should more strictly control of the uric acid level in type 2 diabetes patients with microalbuminuria.